Endoplasmic stress sensor Ire1 is involved in cytosolic/nuclear protein quality control in Pichia pastoris cells independent of HAC1 - Fauzee, Yasmin Nabilah Binti Mohd; Yoshida, Yuki; Kimata, Yukio (Frontiers in Microbiology, 2023)
In eukaryotic species, dysfunction of the endoplasmic reticulum (ER), namely, ER stress, provokes a cytoprotective transcription program called the unfolded protein response (UPR). The UPR is triggered by transmembrane ER-stress sensors, including Ire1, which acts as an endoribonuclease to splice and mature the mRNA encoding the transcription factor Hac1 in many fungal species. Through analyses of the methylotrophic yeast Pichia pastoris (syn. Komagataella phaffii), we revealed a previously unknown function of Ire1. In P. pastoris cells, the IRE1 knockout mutation (ire1) and HAC1 knockout mutation (hac1) caused only partially overlapping gene expression changes. Protein aggregation and the heat shock response (HSR) were induced in ire1 cells but not in hac1cells even under non-stress conditions. Moreover, Ire1 was further activated upon high-temperature culturing and conferred heat stress resistance to P. pastoris cells. Our findings cumulatively demonstrate an intriguing case in which the UPR machinery controls cytosolic protein folding status and the HSR, which is known to be activated upon the accumulation of unfolded proteins in the cytosol and/or nuclei.